APOLIPOPROTEIN MODULATION OF STREPTOCOCCAL SERUM OPACITY FACTOR ACTIVITY AGAINST HUMAN PLASMA HIGH DENSITY LIPOPROTEINS - Rosales, Corina (2009)
Human plasma HDL are the target of streptococcal serum opacity factor (SOF), a virulence factor that clouds human plasma. Recombinant (r) SOF transfers cholesteryl esters (CE) from ~400,000 HDL particles to a CE-rich microemulsion (CERM), forms a cholesterol-poor HDL-like particle (neo HDL), and releases lipid-free (LF) apo A-I. Whereas the rSOF reaction requires labile apo A-I, the modulation effects of other apos is not known. We compared the products and rates of the rSOF reaction against human HDL and HDL from mice over expressing apos A-I and A-II. Kinetic studies showed that the reactivity of various HDL species is apo-specific. LpA-I reacts faster than LpA-I/A-II. Adding apos A-I and A-II inhibited the SOF reaction, an effect that was more profound for apo A-II. The rate of SOF-mediated CERM formation was slower against HDL from mice expressing human apos A-I and A-II than against WT mice HDL, and slowest against HDL from apo A-II over expressing mice. The lower reactivity of SOF against HDL containing human apos is due to the higher hydropathy of human apo A-I, particularly its C-terminus relative to mouse apo A-I, and the higher lipophilicity of human apo A-II. The SOF-catalyzed reaction is the first to target HDL rather than its transporters and receptors in a way that enhances reverse cholesterol transport (RCT). Thus, effects of apos on the SOF reaction are highly relevant. Our studies show that the "humanized" apo A-I-expressing mouse is a good animal model for studies of rSOF effects on RCT in vivo.